Correlation Between Proton Pump Inhibitors and the Complications of Liver Cirrhosis: A Systematic Review and Meta-Analysis - Hwang, Seong Jun; Hyeon Lee, Dong; Koh, Seong-Joon; Kim, Ji Won; Park, Hyun Sun; Kim, Byeong Gwan; Lee, Kook Lae (Turkish Journal of Gastroenterology, 2022)
Background: Many studies and meta-analyses have investigated the associations among proton pump inhibitors (PPIs), spontaneousbacterial peritonitis (SBP), portosystemic encephalopathy (PSE), and other infections. However, these studies had limitations, includingthe omission of several relevant studies and drawing conclusions, based on the abstracts without consulting the full-text of the articles.To evaluate the association between PPIs and complications arising from cirrhosis and risks of PPI use in patients with cirrhosis.Methods: Data were extracted from the EMBASE, PubMed, Cochrane, and Google Scholar databases. The Newcastle-Ottawa scale wasused to assess the quality of the selected studies.Results: A total of 29 studies (13 case–control and 16 cohort studies) involving 20,484 patients were included in the meta-analysis. Thetotal relative risk (RR) for the 23 studies which investigated SBP was 1.31, and the 95% CI was 1.10-1.55 (I2 = 73.0%). The total RR for the7 studies which examined PSE was 1.25 (95% CI 0.85-1.84, I2 = 96.1%). For the 7 studies which analyzed overall infection, the total RRwas 1.37 (95% CI 1.07-1.76, I2 = 79.3%). The RR for the 2 cohort studies that assessed mortality was 1.39 (95% CI 0.85-2.27, I2 = 0.0%).Conclusion: PPI use in cirrhosis patients increased the SBP and overall infection risk. PPIs should be considered with appropriate indications when the benefits exceed the risks in cirrhosis patients with ascites.